Priority order of neonatal colonization by a probiotic or pathogenic Escherichia coli strain dictates the host response to experimental colitis - Hudcovic, Tomas; Petr Hermanova, Petra; Kozakova, Hana; Benada, Oldrich; Kofronova, Olga; Schwarzer, Martin; Srutkova, Dagmar (Frontiers in Microbiology, 2024)
The alarming prevalence of inflammatory bowel disease (IBD) already in early childhood is associated with imbalances in the microbiome, the immune response and environmental factors. Some pathogenic Escherichia (E.) coli strains have been found in IBD patients, where they may influence the progression of the disease. Therefore, the discovery of new harmful bacterial strains that have the potential to drive the inflammatory response is of great importance. In this study, we compared the immunomodulatory properties of two E. coli strains of serotype O6, the probiotic E. coli Nissle 1917 and the uropathogenic E. coli O6:K13:H1. Using the epithelial Caco-2 cell line, we investigated the different abilities of the strains to adhere to and invade epithelial cells. We confirmed the potential of E. coli Nissle 1917 to modulate the Th1 immune response in a specific manner in in vitro setting by stimulating mouse bone marrow-derived dendritic cells. In gnotobiotic in vivo experiments, we demonstrated that neonatal colonization with E. coli Nissle 1917 reaches a stable high concentration in the intestine and protects mice from the progressive effect of E. coli O6:K13:H1 on the development of ulcerative colitis in an experimental model. In contrast, single-dose treatment with E. coli Nissle 1917 is inefficient to achieve such a high concentration and does not protect against the development of DSS-induced ulcerative colitis in mice neonatally colonized with pathobiont E. coli O6:K13:H1. Despite the stable coexistence of both E. coli strains in the intestinal environment of the mice, we demonstrated a beneficial competitive interaction between the early colonizing E. coli Nissle 1917 and the late-arriving strain O6:K13:H1, suggesting its anti-inflammatory potential for the host. This study highlights the importance of the sequence of bacterial colonization, which influences the development of the immune response in the host gut and potentially impacts future quality of life.